Atribuindo sentidos outros pelo WhatsApp : o riso na interatividade audiovisual – “Vôte Prantchei!” - Siqueira, Aline Wendpap Nunes de (2017)
This research is based on the WhatsApp application, through which many audiovisual texts circulate, whose conception, possibility of modification, and redirection imply the reconstruction of the senses, extrapolating the interaction and opening up to innumerable interactive possibilities. And, it is this interactivity to which the focus of this research is directed. Therefore, five audiovisual texts are being analyzed, produced by the interactivity action of the two authors selected for this work, namely: “K-Bça Pensante” e “Xômano que mora logo ali”. What matters is to verify how the modification of the original text, classic or not, to the modified text occurs, as well as what other senses this interactivity engenders. The nature of the modified texts is diverse. For this study, the corpus is restricted to humorous texts. The method is netnographic, that is, it is a research carried out in and on the internet, of qualitative approach, having as its main instrument the analysis of the materials collected. This happens in three stages: film analysis, analysis of elements that provoke laughter and semiological analysis, almost always comparing the selected audiovisual texts and their respective originals. Throughout the process, I turn to Pierre Lèvy and André Lemos for their theoretical basis on cyberculture and cyberspace; Adriana de Souza e Silva (2004) and Sandra Rúbia da Silva (2007) to understand the use of cell phones in contemporary society; to discuss audiovisual production, a wide range of authors– Dancyger (2003), Rabiger (2007), Chion (2008), Zettl (2011), Burch (2011), etc. –; while to think about humor I focused attention especially on the studies of Bergson (1940) and Freud (1903); as for the concepts of interaction and interactivity, the basis is in Primo (2011) and Possari (2009); I have already reported directly on the writings of Iuri Lótman (1979), with additional support in Irene Machado (2007). The historical context is dated, since the research is developed in 2015 and 2016.